Self-Adjoint Operators Generated by Problems of Transmission with Inhomogeneous Conjugation Conditions - Komarenko, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For problems of transmission for higher-order equations with inhomogeneous conjugation conditions, we construct and investigate the corresponding operators in Hilbert spaces. We prove the self-adjointness of these operators for a spectral problem with a parameter in conjugation conditions.